PENGARUH SIKAP TAWAKAL TERHADAP KESTABILAN EMOSI SISWA MADRASAH ALIYAH NEGERI 1 METRO - Sri Andri Astuti (AT-TAJDID, 2018)
This study aims to determine the effect tawakkal towards students’ emotional stability.  Data collection techniques were questionnaires and documentation. The results of the questionnaire were analyzed using product moment correlation analysis techniques using SPSS 16. From the results of hypothesis testing obtained rcount = 0.676> rtable = 2.29 and a significance value of 0,000 <0.05, which means that H0 is rejected and Hi is accepted so that the results of this study are there is an influence of tawakal towards student emotional stability. The higher of tawakal, the higher the emotional stability of the students. Conversely the lower of tawakal, the lower the emotional stability of students. It is important to have a tawakal because through the tawakal a person can fully surrender himself to Allah. High submission to God gives rise to tranquility and peace of mind. Tranquility and peace of mind make one's emotions stable.